Chinese yam vine ceramsite as well as preparation method and application thereof
By using yam vine, fly ash and bentonite as raw materials, horticultural ceramsite was prepared by low-temperature sintering, which solved the problems of insufficient utilization of agricultural waste and high energy consumption in ceramsite preparation. It provides lightweight porous ceramsite for soilless cultivation, promoting plant growth and biomass accumulation.
Patent Information
- Application Number
- CN202511462727.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-14
- Publication Date
- 2025-12-30
AI Technical Summary
In existing technologies, agricultural waste such as yam vines are not effectively utilized, leading to environmental pollution and resource waste. At the same time, traditional ceramsite preparation has problems such as limited raw material acquisition, high sintering temperature, and high energy consumption. Furthermore, research on the preparation of horticultural ceramsite using agricultural and forestry waste as raw materials is relatively scarce.
Horticultural ceramsite was prepared by using yam vine, fly ash and bentonite as raw materials and sintering at low temperature. The specific steps included crushing, sieving, drying, mixing, preheating and high-temperature calcination to prepare lightweight and porous yam vine ceramsite.
This method enables the high-value utilization of agricultural waste, reduces the sintering temperature and energy consumption of expanded clay, and produces horticultural expanded clay with good water retention, air permeability and biocompatibility, which is suitable for soilless cultivation and promotes plant growth and biomass accumulation.
Smart Images

Figure CN121226045A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of agricultural resource recycling, and in particular to a yam vine ceramsite, its preparation method, and its application. Background Technology
[0002] With the acceleration of agricultural modernization in my country and the continuous expansion of planting scale, the amount of agricultural waste generated has also increased dramatically. Among them, planting by-products such as yam vines are rich in polysaccharides, proteins, vitamins, and minerals, and have the potential for resource utilization. However, currently, most of these wastes are randomly discarded or burned in the open, causing serious environmental pollution and resource waste.
[0003] Expanded clay aggregate (ECA), a lightweight porous material, is widely used in horticulture, water treatment, and construction. Traditional ECA is primarily made from shale, clay, and fly ash, which presents challenges such as limited raw material availability, high sintering temperatures, and high energy consumption. In recent years, research on preparing ECA using industrial solid waste has gradually increased, but research on preparing horticultural ECA using agricultural and forestry waste, especially yam vines, as the main raw material remains relatively scarce.
[0004] Foreign countries started earlier in the preparation of ceramsite, mainly using industrial waste (such as sludge, waste glass, and mullite waste) as raw materials, and obtaining high-performance lightweight aggregates through high-temperature sintering. Domestic research has focused more on the ceramsite utilization of solid wastes such as urban sludge, coal gangue, red mud, and steel slag, and has achieved certain results, but there are still problems such as high sintering temperature, complex process, and unstable product performance.
[0005] Against this backdrop, developing a method for preparing horticultural expanded clay granules using yam vine waste as the main raw material, combined with fly ash and bentonite, through low-temperature sintering, can not only realize the high-value utilization of agricultural waste, but also expand the sources of expanded clay granule raw materials and improve the water retention, air permeability and biocompatibility of horticultural substrates, which has important ecological, economic and social significance. Summary of the Invention
[0006] The purpose of this invention is to provide a method for preparing yam vine ceramsite, realizing the recycling of yam vine and the functional design in the field of soilless plant cultivation, and demonstrating the effect of yam vine ceramsite in promoting plant growth and biomass accumulation.
[0007] To achieve the above objectives, the present invention provides the following technical solution:
[0008] This invention provides a yam vine ceramsite, comprising the following raw materials: yam vine, fly ash, and bentonite.
[0009] Furthermore, the mass ratio of the yam vine, fly ash and bentonite is 4:(1-4):(4-5.4).
[0010] The present invention also provides a method for preparing yam vine ceramsite as described in claim 1, wherein yam vine is crushed and sieved to obtain yam vine powder, which is then dried and mixed with fly ash and bentonite, water is added to form spheres, which are then preheated, calcined at high temperature, and cooled to obtain yam vine ceramsite.
[0011] Furthermore, the particle size of the yam vine powder is <1.25 mm.
[0012] Furthermore, the preheating temperature is 105°C, and the preheating time is 120-300 min.
[0013] Furthermore, the calcination temperature is 300-600℃, and the calcination time is 30-90min.
[0014] Furthermore, the fly ash and bentonite are dry powders.
[0015] This invention also provides an application of yam vine ceramsite in soilless cultivation.
[0016] Furthermore, the yam vine ceramic granules are used for soilless cultivation of pothos and peace lilies.
[0017] This invention discloses at least the following technical effects:
[0018] 1. This invention uses agricultural and forestry waste biomass such as yam vine as the main raw material to replace traditional shale and clay in the preparation of ceramsite, alleviating resource pressure and realizing the resource utilization of waste. This invention reduces the sintering temperature of ceramsite to 300-600 ℃, which is about 300 ℃ lower than the sintering temperature of traditional ceramsite, significantly reducing energy consumption and carbon emissions during the sintering process; reducing environmental pollution caused by incineration and landfill, while providing low-cost, high-performance substrates for soilless cultivation, seedling raising, rooftop greening, etc., and promoting the development of green circular agriculture.
[0019] 2. The ceramsite prepared by this invention has a water absorption rate ≥55%, a porosity ≥50%, and a bulk density of 450–460 kg·m³. -3 Lightweight and porous, it retains water and fertilizer and is breathable, making it suitable for crop root growth. Ceramsite contains a certain amount of silicon, aluminum and iron elements, which solidify on the surface of the pellets after sintering, forming a dense glaze layer. The interior forms a porous structure with a high specific surface area, which can effectively protect the matrix and reduce the wear rate. Attached Figure Description
[0020] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0021] Figure 1 The bulk density, apparent density, water absorption rate, and porosity of the yam vine ceramsite prepared in Examples 1-3 are as follows:
[0022] Figure 2 The bulk density, apparent density, water absorption rate, and porosity of the yam vine ceramsite prepared in Examples 4-6;
[0023] Figure 3 The bulk density, apparent density, water absorption rate, and porosity of the yam vine ceramsite prepared in Examples 7-11;
[0024] Figure 4 The bulk density, apparent density, water absorption rate, and porosity of the yam vine ceramsite prepared in Examples 12-16;
[0025] Figure 5 SEM images of the surface of yam vine ceramsite at different magnifications, where a is the surface of yam vine ceramsite at 500x magnification and b is the surface of yam vine ceramsite at 25000x magnification;
[0026] Figure 6 SEM images of cross-sections of yam vine ceramsite at different magnifications, where a is the cross-section of yam vine ceramsite at 500x magnification and b is the cross-section of yam vine ceramsite at 25000x magnification;
[0027] Figure 7 EDS spectrum of the surface of ceramsite in Example 10;
[0028] Figure 8 The image shows the EDS spectrum of the cross-section of the ceramsite in Example 10. Detailed Implementation
[0029] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0030] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0031] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
[0032] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be readily apparent to those skilled in the art. This specification and embodiments are merely exemplary.
[0033] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.
[0034] This invention provides a yam vine ceramsite, comprising the following raw materials: yam vine, fly ash, and bentonite.
[0035] In some embodiments of the present invention, the mass ratio of the yam vine, fly ash and bentonite is 4:(1-4):(4-5.4).
[0036] This invention also provides a method for preparing yam vine ceramsite as described in claim 1. The yam vine is crushed and sieved to obtain yam vine powder, which is then dried, mixed with fly ash and bentonite, and water is added to form spheres. The spheres are then preheated, calcined at high temperature, and cooled to obtain yam vine ceramsite.
[0037] In some embodiments of the present invention, the particle size of the yam vine powder is <1.25 mm.
[0038] In some embodiments of the present invention, the preheating temperature is 105°C and the preheating time is 120-300 min.
[0039] In some embodiments of the present invention, the calcination temperature is 300-600°C and the calcination time is 30-90 min.
[0040] In some embodiments of the present invention, the fly ash and bentonite are dry powders.
[0041] This invention also provides an application of yam vine ceramsite in soilless cultivation.
[0042] In some embodiments of the present invention, the yam vine ceramic granules are used for hydroponics of pothos and peace lilies.
[0043] The preparation method of yam vine ceramic granules according to this invention is as follows:
[0044] 1) Preprocessing stage
[0045] Raw material samples were prepared by drying, grinding, and sieving. First, yam vines were picked out from yam waste and then crushed using a crusher at two-minute intervals. The ground yam vine powder was further sieved to a particle size of <1.25 mm, and then dried in a 105℃ drying oven for 72 hours until constant weight was achieved. Then, yam vine powder, fly ash, and bentonite were mixed with water in different proportions until a paste-like consistency was reached. A suitable amount of the mixture was then hand-rolled into balls.
[0046] (2) Preheating stage
[0047] The hand-rolled raw material balls are placed in a drying oven for drying.
[0048] (3) Sintering stage
[0049] Different sintering temperatures and times were selected to perform high-temperature calcination of the dried ceramic granules using a box-type resistance furnace.
[0050] (4) Cooling stage
[0051] The prepared ceramic pellets were cooled to room temperature.
[0052] Examples 1-3
[0053] Following the above method, three material ratios were selected for the yam vine, fly ash, and bentonite: 4:1:5 (Example 1), 4:2:4 (Example 2), and 3:3:4 (Example 3). A preheating temperature of 105℃ was chosen. The mixture of yam vine powder, fly ash, and bentonite was prepared under the following conditions: drying time of 240 min, sintering temperature of 450℃, and sintering time of 60 min. The resulting yam vine ceramsite was obtained.
[0054] Examples 4-6
[0055] Following the above method, the preheating time was set to 120 min (Example 4), 240 min (Example 5), and 360 min (Example 6) in sequence, and the preheating temperature was selected as 105℃. Yam vine ceramsite was prepared under the conditions of sintering time, sintering temperature, and material ratio of 60 min, 450℃, and 4:2:4, respectively.
[0056] Examples 7-11
[0057] Based on the above method, under the conditions of drying time, sintering time, and material ratio of 240 min, 60 min, and 4:2:4 respectively, the sintering temperature was set to 300℃ (Example 7), 375℃ (Example 8), 450℃ (Example 9), 525℃ (Example 10), and 600℃ (Example 11) to prepare yam vine ceramsite.
[0058] Examples 12-16
[0059] Based on the above method, sintering times of 30 min (Example 12), 45 min (Example 13), 60 min (Example 14), 75 min (Example 15), and 90 min (Example 16) were selected in sequence. Under the conditions of drying time, sintering temperature, and material ratio of 240 min, 450℃, and 4:2:4, respectively, yam vine ceramsite was prepared.
[0060] The performance of the yam vine ceramsite prepared in Examples 1-16 was tested, and the test indicators are as follows:
[0061] (1) Bulk density
[0062] To determine the mass per unit volume of expanded clay aggregate in a packed state, a graduated cylinder was used as the container. The expanded clay aggregate was placed about 50 mm above the cylinder and allowed to fall naturally without colliding with the container walls until the cylinder was completely filled. The top of the cylinder was leveled with a ruler, and then an appropriate amount of small-diameter expanded clay aggregate was used to fill the container. The results were measured three times, and the arithmetic mean was taken as the final result.
[0063] Calculation formula:
[0064] In the formula, —Total mass of expanded clay aggregate and graduated cylinder (kg) —The mass of the graduated cylinder (kg) — Measuring cylinder capacity (L).
[0065] (2) Apparent density
[0066] This method is used to determine the mass per unit volume of ceramsite particles. After drying, the ceramsite sample is thoroughly mixed. A certain mass is placed in a graduated cylinder, and water is added to completely submerge the ceramsite for 1 hour. The sample is then removed and filtered through a sieve for 2 minutes. The ceramsite is poured onto a wrung-out damp towel. Holding both ends of the towel, the ceramsite is placed inside the towel's cavity and rolled back and forth 10 times. The mixture is then poured into a container, and 500 mL of water is added. A known volume of V is used to determine the mass of the ceramsite particles per unit volume. b A container with a volume of (mL) is used to submerge floating ceramic pebbles, and the water level V in the container is read. a (mL), and the arithmetic mean of the three results is taken as the result.
[0067] Calculation formula: (2-2)
[0068] In the formula, —Mass of dried ceramsite sample (g).
[0069] (3) Water absorption rate
[0070] The water absorption rate of expanded clay aggregate in a dry state was determined. The expanded clay aggregate sample was mixed evenly and divided into 3 equal parts. After weighing each part, it was completely immersed in water and the weight was measured. The expanded clay aggregate was then treated on a towel according to the test method for apparent density measurement, and then weighed. The arithmetic mean of the three measurements was taken as the result.
[0071] Calculation formula: (2-3)
[0072] In the formula, —Mass of expanded clay aggregate after soaking in water (g). —Mass of ceramsite during drying (g).
[0073] (4) Porosity
[0074] The porosity between particles of expanded clay was measured under natural stacking conditions.
[0075] Calculation formula: (2-4)
[0076] In the formula, —Bulk density of expanded clay aggregate (kg·m³) -3 ), — Apparent density of expanded clay aggregate (kg·m³) -3 )
[0077] The bulk density, apparent density, water absorption rate, and porosity of the yam vine ceramsite prepared in Examples 1-3 are as follows: Figure 1 As shown in the figure, the water absorption rate and porosity of the three types of ceramsite all show a trend of first increasing and then decreasing with the increase of fly ash ratio. Figure 1 It can be seen that when the material ratio is 4:2:4, both the water absorption rate and the porosity increase, and the bulk density and apparent density are at relatively high values, with the water absorption rate and porosity reaching 57.52% and 49.12%, respectively.
[0078] The bulk density, apparent density, water absorption rate, and porosity of the yam vine ceramsite prepared in Examples 4-6 are as follows: Figure 2 As shown in the figure, the apparent density, bulk density, and porosity of the three types of ceramsite all showed a trend of first increasing and then decreasing with increasing drying time, with drying time having a relatively small effect on bulk density and apparent density. Conversely, the water absorption rate showed a trend of first decreasing and then increasing with increasing drying time. Both bulk density and apparent density reached their peak values of 440.50 kg·m³ at a drying time of 240 min. -3 809.28 kg·m -3 .
[0079] The bulk density, apparent density, water absorption rate, and porosity of the yam vine ceramsite prepared in Examples 7-11 are as follows: Figure 3 As shown in the figure, the apparent density, bulk density, water absorption rate, and porosity of the ceramsite all show a trend of first increasing and then decreasing with the increase of drying time, while the apparent density and bulk density show an increasing trend at 600℃. At 450℃, both the bulk density and apparent density reach their peak values, while the peak values of water absorption rate and porosity occur at 525℃. This indicates that the sintering temperature has a significant impact on the water absorption rate.
[0080] The bulk density, apparent density, water absorption rate, and porosity of the yam vine ceramsite prepared in Examples 12-16 are as follows: Figure 4 As shown in the figure, the apparent density and bulk density of the ceramsite both show a trend of first increasing and then decreasing with increasing sintering time. With increasing time, the strength components of the ceramsite are continuously generated, and its internal structure becomes more compact, thus increasing its strength. Observations show that both the apparent density and bulk density reach their highest values at 60 min. Combined with observations of the glaze formation on the surface of the ceramsite at five different sintering times, the gloss of the glaze layer also becomes more lustrous with increasing time. Under the condition of a sintering time of 60 min, the bulk density and apparent density reach their peak values of 440.50 kg·m³. -3 810.81 kg·m -3 However, the situation was somewhat unique when the sintering time was 30 min. During the water absorption rate measurement, the ceramsite cracked, indicating a particularly high water absorption rate. Ceramsite prepared under other conditions, with a sintering time of 60 min, exhibited higher water absorption and porosity, at 64.58% and 45.66%, respectively.
[0081] Figure 5SEM images of the surface of *Dioscorea nipponica* ceramsite in Example 10 at different magnifications are shown. Image a shows the surface of the ceramsite at 500x magnification, and image b shows the surface at 25,000x magnification. In the 500x magnification image, a relatively rough texture and pores of varying sizes are observed on the surface of the ceramsite. These pores are likely due to the decomposition of organic matter in the *Dioscorea nipponica* powder during high-temperature sintering, generating gases that form pores within the ceramsite. In addition, some irregular granular structures are present on the surface, which may be formed by physicochemical reactions of different components in the raw materials during sintering. Overall, the ceramsite surface exhibits a porous and complex structural feature, which is beneficial for improving its adsorption and moisture retention capabilities. In the 2500x magnification image, the microscopic details of the ceramsite surface are more clearly visible. The images show that the ceramsite surface not only has pores but also some interconnected cracks and pores. These cracks are likely caused by the release of internal stress during sintering. Furthermore, the surface particles exhibit more pronounced morphology, displaying a more complex microstructure. This highly developed pore structure and rough surface provide the expanded clay particles with a larger specific surface area, thereby enhancing their adsorption performance and moisture retention capacity, which is highly advantageous for applications such as hydroponics.
[0082] Figure 6 SEM images of cross-sections of *Dioscorea nipponica* ceramsite from Example 10 at different magnifications are shown. Image a is a 500x magnification cross-section of the *Dioscorea nipponica* ceramsite, and image b is a 25,000x magnification cross-section. In the 500x magnification image, numerous irregularly shaped pores are visible inside the ceramsite. The size and distribution of these pores differ from those observed in the surface images. The cross-sectional images show greater diversity of pores and more complex connections between them, indicating that the internal pore structure of the ceramsite may be more developed than that on the surface. Furthermore, clear boundaries exist between the particles within the ceramsite, which may be due to the melting and solidification behavior of different raw materials during the sintering process.
[0083] In the 2500x cross-sectional SEM image, the internal microstructure of the ceramsite is more clearly revealed. Observation shows that the edges of the pores are relatively rough, while the interior of the pores may contain finer pore structures. These rough pore edges and fine internal pores may provide more adsorption sites for the ceramsite, thereby enhancing its adsorption performance. Simultaneously, the particle morphology and arrangement in the cross-sectional image differ from those observed in the surface image, indicating that the internal structure of the ceramsite may be more complex and significantly influenced by factors such as temperature and pressure during sintering. The difference between the internal and surface pore structures of the ceramsite, with the internal pores potentially being more complex and diverse, contributes to improving the adsorption performance and moisture retention capacity of the ceramsite.
[0084] EDS energy dispersive spectroscopy analysis was performed on the surface and cross-section of the yam vine ceramsite in Example 10 to observe and analyze the elemental distribution and composition inside and outside the ceramsite. The results are as follows: Figure 7 , 8 As shown in Table 1.
[0085] Table 1. Elemental composition of expanded clay aggregate surface and cross-section
[0086]
[0087] The analysis results show that numerous metallic elements are uniformly distributed on the surface of the ceramsite, which can promote adsorption reactions. A comparison revealed that the content of silicon, aluminum, and iron on the surface of the ceramsite differs from that in the cross-section, with relative differences ranging from 0.91% to 4.43%. This difference is likely due to the different morphologies of the compounds formed by these elements during the ceramsite firing process. During the firing process, aluminosilicates melt at high temperatures, forming a liquid phase that serves as the structural basis. This liquid phase is initially uniformly distributed inside the spheres, but gradually migrates to the surface as the firing process progresses. This migration not only inhibits the release of internally generated gas but also solidifies on the surface of the spheres, ultimately forming a dense glaze layer. The formation mechanism of this glaze layer is similar to that formed during high-temperature sliding friction, effectively protecting the substrate and reducing wear.
[0088] Example 17
[0089] Raw material samples were prepared by drying, grinding, and sieving. First, yam vines were selected from yam waste and then pulverized using a crusher at two-minute intervals. The pulverized yam vine powder was further sieved to a particle size <1.25 mm, and then dried in a 105℃ drying oven for 72 hours until constant weight. Then, yam vine powder, fly ash, and bentonite were mixed with water in a 4:2:4 mass ratio until a mud-like consistency was achieved. The mixed material was then hand-rolled into balls. These hand-rolled raw material balls were dried in a drying oven for 229 minutes. The dried ceramsite was then calcined in a box-type resistance furnace at a high temperature of 529℃ for 65 minutes. The ceramsite was then cooled to room temperature. The ceramsite mass was 2.5±0.5 g, and the diameter was 1±0.2 cm.
[0090] Comparative Example 1
[0091] A cultivation substrate, by weight percentage, is a mixture of 50% peat moss, 30% leaf mold, 10% perlite or vermiculite, 5% garden soil, and 5% sand to form a nutrient soil substrate.
[0092] Comparative Example 2
[0093] A traditional method for preparing ceramsite includes the following steps: fly ash and bentonite are mixed with water in a 2:4 ratio until a mud-like consistency is achieved; a suitable amount of the mixed material is hand-rolled into balls; the hand-rolled raw material balls are placed in a drying oven and dried at 105℃ for 240 minutes; the dried ceramsite is then calcined at 525℃ for 60 minutes to produce traditional ceramsite, which is then cooled to room temperature. The diameter of the traditional ceramsite is 1±0.2 cm.
[0094] To verify the effect of the yam vine ceramsite prepared in Example 17 as a cultivation substrate on plant growth, pothos and peace lily were used as experimental materials for verification. The pothos and peace lily were purchased from the Four Seasons Flowers Market in Taigu District, Shanxi Province, and both came from the same batch. The sizes and volumes of the varieties were similar.
[0095] Application Example 1
[0096] The expanded clay pebbles prepared in Example 17 were used as the cultivation substrate for pothos. The experiment was conducted from October 23, 2024 to February 23, 2025 in the laboratory of Shanxi Agricultural University in Taigu District, Shanxi Province. The good lighting and suitable temperature provided a good environment for planting and cultivation.
[0097] Experimental and control groups were set up. The experimental group used the yam vine expanded clay pebbles from Example 17 as the cultivation substrate, while the control group used the nutrient soil substrate from Comparative Example 1. Soil was removed from the roots, the roots were washed with clean water and allowed to dry in a cool, ventilated place. After spraying water to slightly moisten the planting substrate, the plants were transplanted into pots of the same size. Each substrate formula was replicated twice. Maintenance and management conditions were identical; no substrate loosening, fertilization, or pesticide spraying was performed during cultivation. The growth of the pothos plants in each group was observed every 15 days, and indicators such as plant height, number of leaves, and stem diameter were measured.
[0098] The observation indicators and methods are as follows:
[0099] (1) Plant height
[0100] Plant height was measured using a ruler, taking the distance from the base to the top. Unit: cm, accuracy: 0.01.
[0101] (2) Stem is thick
[0102] The diameter of the plant stem at its widest point was measured using electronic vernier calipers. The unit is cm, with an accuracy of 0.01.
[0103] (3) Number of leaves and number of flower buds
[0104] Manual counting.
[0105] (4) Fresh weight
[0106] Weighing was performed using an electronic balance. The unit is g, accurate to 0.0001.
[0107] (5) Dry weight
[0108] The plants were dried in a drying oven, and blanched at 105℃ for 20 minutes. The temperature was then lowered to 80℃ and maintained at a constant temperature until the weight remained constant. After the drying oven had cooled completely, the plant samples were removed and weighed using an electronic balance. Units are in grams, accurate to 0.0001.
[0109] Pothos was cultivated using the compound nutrient soil from Comparative Example 1 and the yam vine ceramsite from Example 17. Plant height, stem diameter, and number of leaves were analyzed, and the results are shown in Table 2. Nutrient soil A was the compound nutrient soil from Comparative Example 1, and yam vine ceramsite B was the yam vine ceramsite from Example 17.
[0110] Table 2. Growth of various morphological indicators in different treatments of pothos plants
[0111]
[0112] Table 3. Average growth of various morphological indicators of pothos under different treatments.
[0113]
[0114] Table 2 shows that the plant height growth of pothos plants, from largest to smallest, is: Treatment B2 > Treatment B1 > Treatment A2 > Treatment A1; the stem diameter growth, from largest to smallest, is: Treatment A1 > Treatment B2 > Treatment B1 > Treatment A2; and the leaf number growth, from largest to smallest, is: Treatment B2 = Treatment A1 > Treatment A2 > Treatment B1. Notably, in group B2, the pothos plants grown with yam vine expanded clay pebbles exhibited negative growth, with one leaf scorching at the tip and eventually withering and falling off. No similar situation was observed in the other treatment groups. This may be due to uneven water distribution or insufficient nutrient supply within the expanded clay pebbles.
[0115] Table 3 shows that the average height increase of pothos plants in treatment B was greater than that in treatment A. Treatment B showed significant height growth throughout the observation period, with an increase of 4.96 cm. The average stem diameter increase was consistent between the two treatments, at 0.115 cm. The average leaf number increase was greater in treatment A than in treatment B, with no significant difference between the two. Overall, the pothos plants treated with yam vine expanded clay pebbles were significantly taller than those treated with nutrient soil, while the differences in stem diameter and leaf number were not significant. This indicates that the excellent physical support and suitable water retention capacity provided by the yam vine expanded clay pebbles promoted stem elongation in the pothos. Yam vine expanded clay pebbles showed certain advantages in promoting pothos growth, especially in terms of plant height increase.
[0116] Pothos was cultivated using the compound nutrient soil from Comparative Example 1 and the yam vine ceramsite from Example 17. The fresh and dry weights and moisture contents of the pothos in different treatment groups were analyzed, and the results are shown in Tables 4 and 5.
[0117] Table 4. Effects of different treatments on the fresh weight and moisture content of dried pothos.
[0118]
[0119] Table 5. Average dry and fresh weight and moisture content of pothos under different treatments.
[0120]
[0121] Table 3 shows that the fresh weight of pothos plants B1 and B2 grown with yam vine expanded clay granules was lower than that of pothos plants A1 and A2 grown in nutrient soil. However, the dry weight of the yam vine expanded clay granule treatment groups was significantly higher than that of the nutrient soil treatment groups. The moisture content of the yam vine expanded clay granule treatment groups B1 and B2 was lower than that of the nutrient soil treatment groups A1 and A2. The dry weights of B1 and B2 in the yam vine expanded clay granule treatment groups were 4.6536 g and 4.5753 g, respectively, while the dry weights of A1 and A2 in the nutrient soil treatment groups were 4.3456 g and 4.5631 g, respectively. This indicates that the pothos plants treated with yam vine expanded clay granules have an advantage in biomass accumulation, and even with a lower fresh weight, they still accumulate more dry matter.
[0122] As shown in Table 4, the water content of the pothos in all treatments reached over 85%, with the water content of the pothos planted with yam vine expanded clay pebbles reaching 85.52% and that of the pothos planted with nutrient soil reaching 87.64%. This indicates that pothos planted with yam vine expanded clay pebbles can accumulate biomass more effectively while maintaining appropriate moisture levels.
[0123] Application Example 2
[0124] Peace lilies were cultivated using traditional expanded clay pebbles (Comparative Example 2) and yam vine expanded clay pebbles (Example 17). Plant height, number of flower buds, and number of leaves were analyzed, and the results are shown in Tables 6 and 7.
[0125] Table 6. Average growth of various morphological indicators in *Spatholobus suberectus* under different treatments.
[0126]
[0127] Table 6 shows that the growth performance of Peace Lily under different substrate treatments differed significantly. In terms of plant height growth, the Peace Lily treated with yam vine expanded clay granules exhibited a stronger growth advantage, with group D1 showing the highest growth at 5.91 cm, while the traditional expanded clay granule group had the lowest at 4.25 cm. This indicates that the yam vine expanded clay granules provided a more favorable growth environment for the Peace Lily, promoting stem elongation. The plant height growth, from largest to smallest, was: Treatment D1 > Treatment D2 > Treatment C2 > Treatment C1. Regarding the increase in flower bud number, the Peace Lily treated with yam vine expanded clay granules also showed an advantage, with groups C2, D1, and D2 tying for the highest increase in flower bud number, all at 3. The increase in flower bud number, from largest to smallest, was: Treatment C2 = Treatment D1 = Treatment D2 > Treatment C1. The increase in leaf number, from largest to smallest, was: Treatment D1 > Treatment D2 = Treatment C1 > Treatment C2. This indicates that the yam vine expanded clay granules not only promoted the vegetative growth of the Peace Lily but also benefited its reproductive growth.
[0128] Table 7. Average growth of various morphological indicators in *Spatholobus suberectus* under different treatments.
[0129]
[0130] Table 7 shows that the average increase in plant height, the average increase in flower bud number, and the average increase in leaf number were all greater in treatment D than in treatment C. Treatment D showed consistently significant growth throughout the observation period, with increases of 5.60 cm in plant height, 3 flower buds, and 6.5 leaves. These results indicate that *Dioscorea nipponica* granules, as a novel soilless cultivation substrate, have the potential to promote the growth of *Spathiphyllum*, especially in increasing plant height and leaf number. This may be related to the porous structure, good water retention, and aeration of *Dioscorea nipponica* granules, which provide a stable growth environment and sufficient nutrient supply for *Spathiphyllum*.
[0131] Peace lilies were cultivated using conventional expanded clay pebbles (Comparative Example 2) and yam vine expanded clay pebbles (Example 17). The fresh and dry weights and moisture contents of the peace lilies in different treatment groups were analyzed, and the results are shown in Table 8.
[0132] Table 8 Effects of different treatments on the fresh weight and moisture content of dried peace lily.
[0133]
[0134] Table 9. Average dry and fresh weight and moisture content of peace lily under different treatments.
[0135]
[0136] Table 8 shows that the fresh weights of Peace Lilies D1 and D2 grown with *Dioscorea cirrhosa* granules were higher than those grown with traditional granules (C1 and C2). The fresh weights of D1 and D2 in the *Dioscorea cirrhosa* granule treatment group were 529.3847 g and 496.5634 g, respectively, while the fresh weights of C1 and C2 in the traditional granule treatment group were 434.8152 g and 487.3847 g, respectively. This result indicates that *Dioscorea cirrhosa* granules may have better water retention and nutrient supply, thereby promoting the growth and biomass accumulation of Peace Lilies. The dry weights of the *Dioscorea cirrhosa* granule treatment group were also significantly higher than those in the traditional granule treatment group. The dry weights of the *Dioscorea cirrhosa* granule treatment group D1 and D2 were 114.6938 g and 109.8156 g, respectively, while the dry weights of the traditional granule treatment group C1 and C2 were 81.9937 g and 84.4526 g, respectively. This significant difference indicates that the peace lilies grown in yam vine expanded clay pebbles accumulated more dry matter during their growth, which may be related to their more effective water and nutrient management. The moisture content of the yam vine expanded clay pebbles D1 and D2 treatment groups was lower than that of the traditional expanded clay pebbles C1 and C2 treatment groups.
[0137] Table 9 shows that the water content of peace lilies grown using "yam vine expanded clay pebbles" reached 78.11%, while that grown using "traditional expanded clay pebbles" reached 81.91%. The increased dry weight indicates that peace lilies grown using yam vine expanded clay pebbles exhibited a higher biomass accumulation capacity during growth. This advantage may stem from better nutrient supply, healthier root development, or more suitable growing conditions. As a novel soilless cultivation substrate, yam vine expanded clay pebbles have demonstrated significant advantages in peace lily cultivation.
[0138] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.
Claims
1. A Dioscoreophyllum yomogo ceramic granule, characterized in that, The raw materials include Dioscorea villosa, fly ash and bentonite.
2. The Dioscoreophyllum pinnatum ceramic according to claim 1, characterized in that, The mass ratio of Dioscorea villosa, fly ash and bentonite is 4: (1-4): (4-5.4).
3. A method of preparing the Dioscoreophyllum pubescens Hiepe ceramic according to claim 1, characterized in that, Dioscorea villosa powder is obtained by crushing and sieving Dioscorea villosa, and then mixed with fly ash and bentonite after drying, and then water is added to form spherical particles, preheated, high-temperature calcined, and cooled to obtain Dioscorea villosa ceramic granules.
4. The method for preparing yam vine ceramsite according to claim 3, characterized in that, The particle size of the Dioscorea villosa powder is less than 1.25 mm.
5. The method for preparing yam vine ceramsite according to claim 3, characterized in that, The preheating temperature is 105 DEG C, and the preheating time is 120-300 min.
6. The method for preparing yam vine ceramsite according to claim 3, characterized in that, The calcination temperature is 300-600 DEG C, and the calcination time is 30-90 min.
7. The method for preparing yam vine ceramsite according to claim 3, characterized in that, The fly ash and bentonite are dry powders.
8. The application of Dioscorea villosa ceramic granules in soilless culture.
9. Use according to claim 8, characterized in that, The Dioscorea villosa ceramic granules are used for soilless culture of green ivy and white palm.